EVALUATION OF LAND USE WITH LAND CAPABILITY CLASSIFICATION USING SATELLITE DATA AND GIS IN BATUR UNESCO GLOBAL GEOPARK - Utama, Putu Wira; Sandi Adnyana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2019)
Development in ??Batur UNESCO Global Geopark has increased significantly in recent years. The land use changes in Bangli regency that the plantation, built-up/residential and tourism support facilities development increased quickly, especially in Kintamani district. To know the suitability of land use in Batur UNESCO Global Geopark area, it is necessary to evaluate land use with land capability classification. Landsat 8 remote sensing data on 27 September 2017 was used to create land use maps. Land use maps obtained through the process of image classification using supervised classification method and verified by ground check, this technique result 10 classes of land use. Land capability class map generated from improvisation overlay methods, reclassification of differentiator classes into the differentiator value of a raster data pixel (differentiator pixel value method). Furthermore, to evaluate of land use suitability was conducted by comparing land use with land capability class. In this process, there is an overlay between the land use maps with land capability class map using geographic information system (GIS). The results of evaluation land use in Batur UNESCO Global Geopark with land capability class overall has suitable area 15,764.78 ha (88.49%), not suitable area 1,767.48 ha (9.92%) and not detected/cloud interference 283.67 ha (1.59%).